FOLFOX vs. FOLFIRI in Colorectal Adenocarcinoma: A Retrospective Study of Treatment Patterns, Side Effects, and Treatment Response - Putu Ananda Sutiksna Mulya; Bagus Komang Satriyasa; Ni Wayan Sucindra Dewi; Desak Ketut Ernawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Colorectal adenocarcinoma (CRC) is a prevalent malignancy with a high recurrence rate, necessitating multimodal treatment strategies. Chemotherapy regimens like FOLFOX (folinic acid, fluorouracil, oxaliplatin) and FOLFIRI (folinic acid, fluorouracil, irinotecan) are crucial components of this approach. This study aimed to analyze treatment patterns, side effects, and treatment response of FOLFOX and FOLFIRI in a real-world cohort of CRC patients. Methods: A retrospective observational study was conducted on CRC patients who received FOLFOX or FOLFIRI between January 2020 and December 2023. Data on demographics, disease stage, chemotherapy regimen, side effects, comorbidities, and treatment response were collected from electronic medical records. Results: A total of 146 patients were included. The majority were male (57.5%) with a mean of age 58.4 years. Most tumors were located in the rectum and sigmoid (75.3%), with over 50% of patients presenting with stage IV disease. FOLFIRI was the most common regimen (45.9%), followed by FOLFOX (36.3%). Common side effects included nausea, vomiting, decreased appetite, and hair loss. Hypertension was the most prevalent comorbidity. A total of 79.5% of patients were alive after chemotherapy. Conclusion: This study provides insights into the real-world treatment patterns and outcomes of FOLFOX and FOLFIRI in CRC patients. The choice of regimen appears to be influenced by factors such as disease stage and patient characteristics. Further research is needed to compare the efficacy and safety of these regimens and identify optimal treatment strategies for specific patient subgroups.